SOME CONSIDERATIONS REGARDING THE SERVICE SECTOR - Nasirov Jaloliddin (European Science Publishing, 2024)
The article presents some notes that today in our republic "there is a rapid development of the service sector, an increase in the role and share of services in the formation of the domestic product, a radical change in the composition of services provided, primarily due to their modern high-tech types.""this is considered an urgent matter.
Keywords: innovative development, service, infrastructure, service market, production.